PENGARUH PERENDAMAN DALAM LARUTAN ASAMSITRAT pH 3 TERHADAP KEBOCORAN MIKRO RESTORASI RESIN KOMPOSIT BULK-FILL KAVITAS KELAS I - , ASTRID NUR ANISAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Microleakage on resin composites restoration is a gap formed between cavity wall and the restoration caused by contraction during polymerization and aging process. Acid is one of much kind of exposures inflicting aging and resin composites degradation process. Bulk-fill resin composites are one kind of resin composites that are famous recently by the 4 mm depth of cure in single increment and it has lower polymerization shrinkage compared by conventional resin composites. The information about effect of acid on microleakage of bulkfill resin composites restoration has not been well provided so that this study aimed to determine the effect of immersion in citric acid solution with pH 3 to the microleakage of class I cavity bulk-fill resin composites restoration. This study used 20 class I cavity prepared first maxilla premolars (diameter: 4 mm, depth: 4mm) which filled by bulk-fill composites in single increment. The sample group was divided into two groups of ten which group I immersed in artificial saliva for 24 hours and the group II was immersed in citric acid solution with pH 3 for 15 days. Measurement of microleakage in this study used active staining methods, which specimens immersed in 2% methylene blue and then centrifuged in 3000 rpm for 5 minutes. Observation firstly done by dissecting the tooth longitudinally performed by Isomet Low Speed Saw and then observed by stereomicroscope with 50 times magnification. The study results showed that there is a significant difference of mean rank between the two sample groups (p<0,05), group I (7,65) and group II (13,35). Based on these results, a conclusion could be withdrawn that citric acid with pH 3 solution could cause microleakage on bulk-fill resin composite class I restoration. Keywords: microleakage, citric acid, degradation, aging